Desafios e possibilidades do ensino a distância no Tocantins: um estudo de caso do curso de Administração Pública a distância da UFT - Leal, Teomar Manduda Aires (Universidade Federal do Tocantins, 2016)
The Open University System of Brazil (UAB) is a network system that articulates institutions of public Higher Education, cities and states to expand and incorporate the offer of distance modality of Higher Education. The general purpose of the research was to comprehend the process of teaching/learning in distance education, viewed by students, managers, tutors and teachers at Public Administration UAB of the UFT. To reach the objectives proposed, the exploratory and descriptive study of case was chosen, by means of qualitative and quantitative approach. The sample was compounded by: 316 students, 70 tutors, 9 teachers, the course coordinator and the Principal. The first step consisted in a survey fulfilled by students; the second was based in interviews with the managers (management and guidance) of the course studied; the third step was to realize a survey with tutors and professors. In general, the results were positive, in most of the measured factors. The students well evaluated the physical and technologic structures of the poles. The problems of interaction deserve attention, however the percentage of critics was not that meaningful. The research enabled a diagnosis which will provide to the managers of the course and the distance education system (EaD) together subsidies to trace strategies for the improvement of the course and satisfaction of the involved.